The Impact of Professional Degree Graduate Expansion on Regional Innovative Human Capital - Xiulin Gu; Tao Zhang; Hao Yao; Jianxing Lu; Bin Wang; Ya Gu (SAGE Open)
Based on the panel data of 31 Chinese provinces and cities from 2010 to 2019, the study examines the impact of professional degree graduate students on regional innovation human capital and investigated the threshold effect of human capital spatial agglomeration through panel fixed-effects model, GMM dynamic panel model, quantile regression and threshold regression model. It was found that (1) Since 2010, the expansion of graduate education in mainland China has been primarily in professional degree programs, with the proportion of professional degree graduate students increasing from 24% to 58%. (2) The expansion of professional degree graduate programs contributes to the accumulation of innovative human capital in the region, with increasing marginal benefits. (3) The agglomeration effect of human capital is significant; the impact of the expansion of professional degree graduate programs on regional innovative human capital increases with urban population density.